Geodetic support for monitoring changes in the land use structure of Ukraine during the period of russian armed aggression and post-conflict recovery - Domashenko, H.; Monar D, S.; Prokopenko, N. (Land Management, Cadastre and Land Monitoring, 2025)
This article examines the geodetic support for monitoring land use changes in Ukraine during the war and post-war periods, which is a key element of national security, economic development, and social stability. The purpose of the article is to present an analysis of the current state and future development prospects of geodetic support for monitoring land resources. The research employs a comprehensive approach, including an analysis of scientific publications and practical examples of geodetic technologies used to monitor land use changes during armed conflict and the post-war reconstruction of Ukrainian territories. The practical research was based on land use in the Bilokrynytsia territorial community in the Rivne region. The study explores the use of Global Navigation Satellite Systems (GNSS), remote sensing (RS), and unmanned aerial vehicles (UAVs), which enable near real-time detection of land use changes and the effective use of geospatial data for decision-making. Special attention is given to LiDAR technologies that enable the creation of high-precision three-dimensional models of the Earth’s surface and the identification of degradation processes, particularly in geographically complex environments. Hybrid positioning is discussed as well, integrating various data sources (satellite, radio frequency, inertial sensors, visual data) to enhance accuracy and reliability, especially under conditions of limited visibility or satellite signal blockage. The study emphasizes that the processing and interpretation of geodetic data includes preprocessing, spatial localization, GIS analysis and modeling, and the generation of cartographic materials. The practical significance lies in providing objective and up-to-date data for making informed decisions on land use, spatial planning, and emergency response. It is concluded that further research is needed to improve the use of digital technologies, automate data collection, and integrate various sources into GIS systems for reliable land use change monitoring during both active hostilities and reconstruction phases. Keywords: geodetic support, monitoring, land use, war, post-war period, GIS, GNSS, UAV, remote sensing.